Sustainable management for woody crops in Maditerranean dry-lands - Fernandez Zamudio, M.A.=700 1 De Miguel, M.D.
(Es, En)
ilus., 31 ref.
Keywords: CULTIVOS; SOSTENIBILIDAD; AGUA DE RIEGO; CAMBIO TECNOLOGICO; ESPAÑA; AGROSISTEMAS; CULTIVOS LEÑOSOS